1994
DOI: 10.1046/j.1365-313x.1994.6060893.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the cucumber malate synthase gene promoter by transient expression and gel retardation assays

Abstract: SummaryRecently it has been demonstrated that the singlecopy malate eynthase (MS) and ieocitreta lyase (ICL) genes from cucumber are regulated by nutritional

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…Promoter analyses of sugar-starvation-inducible genes, such as malate synthase (Graham et al 1994, Sarah et al 1996, a-amylase (Hwang et al 1998, Lu et al 1998, Toyofuku et al 1998) and a photosynthetic gene (Urwin and Jenkins 1997) have identified several cis-regulatory sequences. However, none of these putative cis-regulatory elements was found in the promoter regions of Arabidopsis E1b and E2 genes.…”
Section: Discussionmentioning
confidence: 99%
“…Promoter analyses of sugar-starvation-inducible genes, such as malate synthase (Graham et al 1994, Sarah et al 1996, a-amylase (Hwang et al 1998, Lu et al 1998, Toyofuku et al 1998) and a photosynthetic gene (Urwin and Jenkins 1997) have identified several cis-regulatory sequences. However, none of these putative cis-regulatory elements was found in the promoter regions of Arabidopsis E1b and E2 genes.…”
Section: Discussionmentioning
confidence: 99%
“…In our cucumber study, two highly conserved germination-response elements (IMHI and IMH2) were identified in the CsPCK gene as being necessary for germination and, possibly, senescence. Although the biological function of the IMHI sequence is not yet clear, similar sequences have been shown in fungi (Neurospora crassa) and yeast (Saccharomyces cerevisiae), suggesting that it may be required for either a sugar response (starvation) or germination response (Graham et al, 1994). The IMH2 sequences (with similarity to MYB binding sequences) in the icl, ms, and CsPCK promoters might direct the carbohydrate regulation of expression for many plant genes (Graham eta[., 1994;Grotewold et al, 1994).…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, controlling intracellular sugar levels is a central element for the regulation of metabolic pathways in living cells. Many of the genes associated with carbon assimilation and sugar transport are directly or partly regulated by fluxes in the sugar levels of target cells and tissues (Sheen, 1990;Graham et al, 1994;Koch, 1996;Sherson et al, 2000). Because of this, the metabolic regulation of plant gene expression is now a central focus in studying the plant sugartransport mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that high levels of metabolizable carbohydrates can cause repression in the transcription of these genes in cultured plant cells (Kudielka et al, 1981;Theimer, 1983a, 1983b;Graham et al, 1992Graham et al, , 1994a. Because distinct DNA sequences play roles in activating the isocitrate lyase gene in developing seed and seedlings, it seems unlikely that its expression is controlled solely by carbohydrate levels.…”
Section: Several Dna Sequences Regulate the Lsocitrate Lyase Gene Durmentioning
confidence: 99%